Money for nothing - Musca, Tom; Menendez, Ramon (Burbank, California Hollywood Pictures Home Video, 1994)
After finding a bagful of unmarked (dollar sign)100 bills, there were a million reasons for unemployed dockwater Joey Coyle to give the money back, but he couldn't think of one! And when he decides to keep it, oh what a price he pays! The lucky discovery launches a buying spree and a series of uproarious events leading to Joey's outrageous attempt at sneaking out of the country past the media, the mob and the cops!
Screenplay by Ramon Menendez & Tom Musca and Carol Sobieski ; Executive producers, David Permut, Gordon Freedman, Matthew Tolmach.
John Cusack, Michael Madsen, Debi Mazar, Benicio Del Toro, Michael Rapaport, Maury Chaykin, James Gandolfini, Fionnula Flanagan.
Dolby digital
In English.
Keywords: Feature films